Assessment of the nutritional qualities of ten botanicals used in pregnancy and child delivery in Ibadan, Nigeria - Idayat Titilayo Gbadamosi; Otobo ER (International Journal of Phytomedicine, 2014)
Ten botanicals used in pregnancy and child delivery by traditional maternity experts in Ibadan were analysed for their nutrient and phytochemical constituents to provide scientific insight into their therapeutic uses. The nutrient and phytochemical analyses of powdered plant samples were done using standard methods. The plants contained phosphorus, calcium, iron, manganese, magnesium and zinc in varied quantity. Eleusine indica (165.0mg/100g) was highest in calcium content and Croton zambesicus (40.0mg/100g) had the least. Iron content was 9.7mg/100g in E. indica and Uraria picta had 2.7mg/100g. The protein content of plant samples varied between 13.95% and 18.30%, the highest (18.30%) being in Phyllantus niruri and Clerodendrum volubile (13.95%) the least. The carbohydrate value ranged between 45.75% (U. picta) and 52.60% (C. volubile). Crude fibre was 17.80% in Xylopia aethiopica and C. volubile contained 13.50%. All plants contained alkaloids, cerotenoids, flavonoids, saponins and steroids. The plants have significant nutritional properties in addition to phytochemical constituents. The nutrients could support the increased energy and nutritional requirements in pregnancy, prevent malnutrition and supplement the phytochemicals in therapeutic activities. Toxicological studies of the plants would confirm their safety in administration.